Should we clash or should we go? The impact of low wage and bad working conditions on the exit-voice trade-off - Olivier Godechot; Zinaida Salibekyan (Max Planck Sciences Po Center on Coping with Instability in Market Societies (MaxPo), 2013)
Although Hirschman's exit-voice theoretical model has been applied to labor markets, research up to now has not tested one of its most important features: the impact of job quality on exit-voice strategies. Hirschman's model of consumer behavior explains that those individuals unsatisfied with a product's quality are more likely to "voice", whereas those more concerned with its price are more likely to "exit". A rationale for this tradeoff is based on information: first, information on the price of alternative options is much more accessible than information on quality; second, voice produces more information than exit and favors opportunities for specific improvements. We transpose Hirschman's assumptions to labor markets and use the French SalSa survey and DADS, declaration by employers on social data, to examine the conditions under which French employees are more likely to exit, and the conditions under which they are more likely to voice. Our results support the Hirschmanian hypothesis. A deterioration by one unit in our working-conditions index increases the probability of participation in collective action by 5 percentage points. An increase in log hourly wage by one unit decreases the probability of quitting by 5 percentage points.
Keywords: 330